Awareness of age-related change, chronological age, subjective age and proactivity: An empirical study in China - Zhang, Wanli; Wood, Stephen (Frontiers in Psychiatry, 2022)
An ageing workforce and the increasing value placed on employees’ proactivity are two important features of current workplaces. We thus address the extent to which this proactivity is affected by age and ageing. The study has two objectives. First, it aims to validate the concept of awareness of age-related change in the Chinese context. Second, it compares the explanatory power of awareness of age-related change with that of chronological age and subjective age in predicting three types of proactivity: task proactivity, development proactivity and organization proactivity. We used a ten-item awareness of age-related change instrument in a survey of school teachers (n=421) in China, and validated its content by comparing the responses of a subsample of these teachers (n=33) to questions asked in a semi-structured interview. This confirmed the validity of the instrument’s content, and its applicability beyond North America and Europe, in a Chinese context. We then show that awareness of positive and negative age-related changes are, respectively, positively and negatively associated with the three types of proactivity, and that they are better predictors than chronological age and subjective age. The research adds weight to challenges to negative age stereotyping ‒ that older employees are set in their ways and less proactive ‒ and to claims of the value of awareness of age-related change as a key measure of ageing, by showing that this factor can predict outcomes beyond health and the concerns of the older adults.